PENGARUH BUDAYA ORGANISASI DAN PERILAKU KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PUSKESMAS NGALI - Fadillah, Marisa; Abidin, Zainal; Wahyulina, Sri (Jurnal Magister Manajemen, 2023)
This study aims to determine the effect of organizational culture and leadership behavior on the performance of employees of the Ngali Health Center in Bima district. This study consists of 2 independent variables, namely organizational culture (X1) and leadership behavior (X2) and the dependent variable, namely performance (Y). the type of research used is associative-causal research. the population in the study were all employees of the Ngali Public Health Center in Bima district, totaling 70 employees. The show that organizational culture has a positive and significant effect on the performance of employees of the Ngali Health Center in Bima district. Leadership behavior has a positive and significant effect on the performance of Ngali Public Health Center employees in Bima district.